A polyurethane composite material and its preparation method and application

By adding flame retardant and modified hydroxyapatite to the polyurethane composite material, the problems of flammability and insufficient bonding strength of thermoplastic polyurethane materials are solved, and the flame retardancy and mechanical properties of the material are significantly improved.

CN119505519BActive Publication Date: 2025-04-25HUNAN QIANGTAI NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510087979.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

Thermoplastic polyurethane materials have limited their application in many fields due to their low limit oxygen index and are flammable, and their binding strength with reinforcement materials is insufficient.

Method used

A polyurethane composite material is used, including thermoplastic polyurethane elastomer, glass fiber, flame retardant, modified hydroxyapatite, dispersant, antioxidant and mold release agent, and the flame retardant and mechanical properties of the material are improved through the interaction of the dual flame retardant mechanism and the modified material.

Benefits of technology

The flame retardant and mechanical properties of polyurethane composite materials have been significantly improved, meeting the wider application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the technical field of polymer materials, and in particular to a polyurethane composite material and a preparation method and application thereof. The polyurethane composite material comprises the following raw materials in parts by weight: 45-65 parts of thermoplastic polyurethane elastomer, 20-30 parts of glass fiber, 10-15 parts of flame retardant, 1-5 parts of modified hydroxyapatite, 1-1.5 parts of dispersant, 1-1.5 parts of antioxidant, and 1-3 parts of release agent. Raw materials such as flame retardant and modified hydroxyapatite are added to the polyurethane composite material, wherein the flame retardant can improve the flame retardancy of the polyurethane composite material through a dual flame retardant mechanism, and the modified hydroxyapatite is conducive to improving the overall mechanical properties of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a polyurethane composite material and a preparation method and application thereof. Background Art

[0002] Thermoplastic polyurethane (TPU) elastomer is a (AB)n block linear polymer, consisting of a flexible soft segment and a rigid hard segment. A is a polyester or polyether with a high molecular weight (1000-6000), B is a diol containing 2-12 straight-chain carbon atoms, and the chemical structure between the AB segments is diisocyanate. Due to its high modulus, high strength, excellent wear resistance, chemical resistance and other advantages, it is often mixed with reinforcing materials such as glass fiber and used in the preparation of transmission towers, communication towers and street light poles.

[0003] However, due to the limitation of its chemical structure, thermoplastic polyurethane has a low limiting oxygen index and is extremely flammable. In addition, it is accompanied by toxic smoke and molten dripping when burning, which poses a major threat to people, property and the environment. The flammability of thermoplastic polyurethane limits its application in many fields. Therefore, it is necessary to improve the flame retardancy of thermoplastic polyurethane. In addition, although the blending of reinforcing materials can improve the performance of polyurethane composites, their affinity with polyurethane is weak, and the bonding strength of polyurethane composites needs to be improved. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, one of the objectives of the present invention is to provide a polyurethane composite material having good flame retardant properties and mechanical properties.

[0005] The second object of the present invention is to provide a method for preparing a polyurethane composite material, which is simple to prepare.

[0006] The third object of the present invention is to provide an application of a polyurethane composite material, which has broad application prospects.

[0007] One of the purposes of the present invention is achieved by the following technical solution:

[0008] A polyurethane composite material comprises the following raw materials in parts by weight: 45-65 parts of thermoplastic polyurethane elastomer, 20-30 parts of glass fiber, 10-15 parts of flame retardant, 1-5 parts of modified hydroxyapatite, 1-1.5 parts of dispersant, 1-1.5 parts of antioxidant, and 1-3 parts of release agent;

[0009] The preparation method of the flame retardant is as follows:

[0010]

[0011] 3-methylsulfonyl-1H-1,2,4-triazole-5-amine, triethylamine and dichloromethane are uniformly mixed to obtain a mixed solution; a dichloromethane solution of 2,3,6,7,10,11-hexabromotriphenylene is added to the mixed solution for reaction, and after the reaction is completed, the flame retardant is obtained by purification.

[0012] Preferably, the molar ratio of the 3-methylsulfonyl-1H-1,2,4-triazole-5-amine, triethylamine and 2,3,6,7,10,11-hexabromotriphenylene is (6-6.5):(7-8):1; the molar concentration of 3-methylsulfonyl-1H-1,2,4-triazole-5-amine in the mixed solution is 0.5-0.6 mol / L; the molar concentration of 2,3,6,7,10,11-hexabromotriphenylene in the dichloromethane solution of 2,3,6,7,10,11-hexabromotriphenylene is 0.2-0.5 mol / L; the reaction temperature is 0-5°C, and the reaction time is 8-10 h.

[0013] Preferably, the preparation process of the modified hydroxyapatite is as follows:

[0014] The pretreated lignin is dispersed in deionized water, and then hydroxyapatite and magnesium chloride are added to obtain a mixed solution; after adjusting the pH of the mixed solution, the mixed solution is reacted at room temperature, and after the reaction is completed, the mixed solution is purified to obtain the mixed solution.

[0015] Preferably, the mass ratio of magnesium chloride, pretreated lignin and hydroxyapatite is 1:(2-5):(2-5); the pH of the mixed solution is adjusted to 8-9; and the reaction time is 12-18 hours.

[0016] Preferably, the preparation process of the pretreated lignin is as follows:

[0017] According to the dosage ratio of kraft lignin and 1,4-dioxane aqueous solution of 1g: (45-55)mL, kraft lignin and 1,4-dioxane aqueous solution are mixed evenly, and then ozone is introduced into the mixture for reaction for 0.5-1.5h. After the reaction is completed, the mixture is purified to obtain the product; the volume ratio of 1,4-dioxane to deionized water in the 1,4-dioxane aqueous solution is 9:1.

[0018] Preferably, the dispersant is vinyl bisstearamide, the antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, and the release agent is Taoxi 3527.

[0019] Preferably, the length of the glass fiber is 25-50 mm.

[0020] The second object of the present invention is achieved by adopting the following technical solution:

[0021] The preparation method of the polyurethane composite material comprises the following steps:

[0022] The raw materials are mixed according to the weight ratio of each raw material, and then poured and cured to form.

[0023] Preferably, the stirring temperature is 160-175° C., the stirring time is 10-15 h, and the stirring speed is 250-500 rpm.

[0024] The third object of the present invention is achieved by adopting the following technical solution:

[0025] The polyurethane composite material is applied to transmission towers.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The polyurethane composite material of the present invention includes raw materials such as flame retardants and modified hydroxyapatite. Among them, the flame retardant can improve the flame retardancy of the polyurethane composite material through a dual flame retardant mechanism. Specifically, the flame retardant contains 1,2,4-triazole groups, sulfonyl groups and benzene rings. On the one hand, these groups improve the flame retardancy of the polyurethane composite material by promoting the formation of carbon black; on the other hand, they can also improve the flame retardancy of the polyurethane composite material by diluting and inhibiting the release of combustible gases. The surface of the modified hydroxyapatite of the present invention is rich in active sites such as carboxylic acids, hydroxyls and magnesium ions. These active sites can interact with the polyurethane matrix and glass fibers. This interaction not only enhances the compatibility between the components, but also promotes more uniform dispersion and filling of the components, which is beneficial to improving the overall mechanical properties of the composite material.

[0028] 2. The polyurethane composite material of the present invention has excellent flame retardant properties and mechanical properties. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with and specific embodiments. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0030] The length of the glass fiber involved in the present invention is 25-50 mm.

[0031] 1. Embodiment

[0032] Example 1

[0033] Example 1 provides a polyurethane composite material, which is composed of the following raw materials in parts by weight: 50 parts of thermoplastic polyurethane elastomer, 25 parts of glass fiber, 12 parts of flame retardant, 3 parts of modified hydroxyapatite, 1.2 parts of vinyl bisstearamide, 1.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 2 parts of Taoxi 3527.

[0034] The preparation method of the above flame retardant is as follows:

[0035]

[0036] According to the molar ratio of 3-methylsulfonyl-1H-1,2,4-triazole-5-amine, triethylamine and 2,3,6,7,10,11-hexabromotriphenylene of 6:7:1, 3-methylsulfonyl-1H-1,2,4-triazole-5-amine and triethylamine were added to dichloromethane to obtain a mixed solution (the molar concentration of 3-methylsulfonyl-1H-1,2,4-triazole-5-amine was 0.5 mol / L); then, a dichloromethane solution of 2,3,6,7,10,11-hexabromotriphenylene (the molar concentration of 2,3,6,7,10,11-hexabromotriphenylene was 0.3 mol / L) was added dropwise to the mixed solution at 4°C for 9 hours. After the reaction was completed, a crude product was obtained by filtration. The crude product was washed with dichloromethane, dissolved in deionized water, precipitated in anhydrous ethanol, and dried in vacuo at 50°C for 24 hours to obtain a flame retardant.

[0037] The NMR results of flame retardants are:

[0038] 1 H-NMR (400 MHz, DMSO) δ = 2.96 (s, 18H), 8.27 (s, 6H), 8.90 (s, 6H), 9.62 (s, 6H); mass spectrometry analysis MS (ESI+): [M+H]+ calculated as 1189.13, found as 1189.13; the above results confirmed that the obtained product was the target product.

[0039] The preparation process of the modified hydroxyapatite is as follows:

[0040] According to the dosage ratio of kraft lignin and 1,4-dioxane aqueous solution 1g:50mL, kraft lignin and 1,4-dioxane aqueous solution (v / v=9:1) were mixed evenly in a glass column reactor, and then heated at 1L·min -1 ozone was introduced into the reaction chamber at a rate of 1 h, and after the reaction was completed, a filtrate was obtained by suction filtration, and the filtrate was subjected to rotary evaporation to remove all solvents to obtain a solid product, and the solid product was washed with water and vacuum dried to obtain the pretreated lignin;

[0041] According to the mass ratio of magnesium chloride, pretreated lignin and hydroxyapatite of 1:3:3, the pretreated lignin was ultrasonically dispersed in deionized water, and then hydroxyapatite and magnesium chloride were added to obtain a mixed solution; the pH of the mixed solution was adjusted to 8.5, and the mixture was reacted at room temperature for 15 hours. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain modified hydroxyapatite.

[0042] Example 1 also provides a method for preparing the polyurethane composite material, which is as follows:

[0043] Add each raw material into a stirrer according to the weight ratio of each raw material, stir at 170°C and 300 rpm for 12 hours to obtain a mixture, pour the mixture into a mold, and vacuum degas and solidify to form.

[0044] Example 2

[0045] Example 2 provides a polyurethane composite material, which is composed of the following raw materials in parts by weight: 45 parts of thermoplastic polyurethane elastomer, 20 parts of glass fiber, 10 parts of flame retardant, 1 part of modified hydroxyapatite, 1 part of vinyl bisstearamide, 1 part of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 1 part of Taoxi 3527.

[0046] The preparation method of the above flame retardant is as follows:

[0047]

[0048] According to the molar ratio of 3-methylsulfonyl-1H-1,2,4-triazole-5-amine, triethylamine and 2,3,6,7,10,11-hexabromotriphenylene of 6.5:8:1, 3-methylsulfonyl-1H-1,2,4-triazole-5-amine and triethylamine were added to dichloromethane to obtain a mixed solution (the molar concentration of 3-methylsulfonyl-1H-1,2,4-triazole-5-amine was 0.5 mol / L); Then, a dichloromethane solution of 2,3,6,7,10,11-hexabromotriphenylene (the molar concentration of 2,3,6,7,10,11-hexabromotriphenylene is 0.2 mol / L) was added dropwise to the mixed solution at 0°C for 10 hours. After the reaction was completed, a crude product was obtained by filtration. The crude product was washed with dichloromethane and then dissolved in deionized water and precipitated in anhydrous ethanol. The flame retardant was obtained after vacuum drying at 50°C for 24 hours.

[0049] The preparation process of the modified hydroxyapatite is as follows:

[0050] According to the dosage ratio of kraft lignin and 1,4-dioxane aqueous solution 1g:45mL, kraft lignin and 1,4-dioxane aqueous solution (v / v=9:1) were mixed evenly in a glass column reactor, and then heated at 1L·min-1 ozone was introduced into the reaction chamber at a rate of 1.5 h for reaction. After the reaction was completed, the filtrate was filtered to obtain a filtrate. The filtrate was evaporated by rotary evaporation to remove all solvents to obtain a solid product. The solid product was washed with water and vacuum dried to obtain the pretreated lignin.

[0051] According to the mass ratio of magnesium chloride, pretreated lignin and hydroxyapatite of 1:2:2, the pretreated lignin is ultrasonically dispersed in deionized water, and then hydroxyapatite and magnesium chloride are added to obtain a mixed solution; the pH of the mixed solution is adjusted to 8, and the mixture is reacted at room temperature for 12 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain modified hydroxyapatite.

[0052] Example 2 also provides a method for preparing the polyurethane composite material, which is as follows:

[0053] Add the raw materials into a stirrer according to the weight ratio of each raw material, stir at 160° C. and 250 rpm for 15 h to obtain a mixture, pour the mixture into a mold, and vacuum degas and solidify to form.

[0054] Example 3

[0055] Example 3 provides a polyurethane composite material, which is composed of the following raw materials in parts by weight: 65 parts of thermoplastic polyurethane elastomer, 30 parts of glass fiber, 15 parts of flame retardant, 5 parts of modified hydroxyapatite, 1.5 parts of vinyl bisstearamide, 1.5 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 3 parts of Taoxi 3527.

[0056] The preparation method of the above flame retardant is as follows:

[0057]

[0058] According to the molar ratio of 3-methylsulfonyl-1H-1,2,4-triazole-5-amine, triethylamine and 2,3,6,7,10,11-hexabromotriphenylene of 6:7:1, 3-methylsulfonyl-1H-1,2,4-triazole-5-amine and triethylamine were added to dichloromethane to obtain a mixed solution (the molar concentration of 3-methylsulfonyl-1H-1,2,4-triazole-5-amine was 0.6 mol / L); then, a dichloromethane solution of 2,3,6,7,10,11-hexabromotriphenylene (the molar concentration of 2,3,6,7,10,11-hexabromotriphenylene was 0.5 mol / L) was added dropwise to the mixed solution at 5°C for 8 hours. After the reaction was completed, a crude product was obtained by filtration. The crude product was washed with dichloromethane, dissolved in deionized water, precipitated in anhydrous ethanol, and dried in vacuum at 50°C for 24 hours to obtain a flame retardant.

[0059] The preparation process of the modified hydroxyapatite is as follows:

[0060] According to the dosage ratio of kraft lignin and 1,4-dioxane aqueous solution 1g:55mL, kraft lignin and 1,4-dioxane aqueous solution (v / v=9:1) were mixed evenly in a glass column reactor, and then heated at 1L·min -1 ozone was introduced into the reaction chamber at a rate of 0.5 h. After the reaction was completed, the filtrate was filtered to obtain a filtrate. The filtrate was evaporated by a rotary evaporator to remove all solvents to obtain a solid product. The solid product was washed with water and vacuum dried to obtain the pretreated lignin.

[0061] According to the mass ratio of magnesium chloride, pretreated lignin and hydroxyapatite of 1:5:5, the pretreated lignin is ultrasonically dispersed in deionized water, and then hydroxyapatite and magnesium chloride are added to obtain a mixed solution; the pH of the mixed solution is adjusted to 9, and the mixture is reacted at room temperature for 12 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain modified hydroxyapatite.

[0062] Example 3 also provides a method for preparing the above polyurethane composite material, which is as follows:

[0063] Add the raw materials into a stirrer according to the weight ratio of each raw material, stir at 175° C. and 500 rpm for 10 hours to obtain a mixture, pour the mixture into a mold, and vacuum degas and solidify to form.

[0064] 2. Comparative Example

[0065] Comparative Example 1

[0066] The difference between Comparative Example 1 and Example 1 is that 2,3,6,7,10,11-hexabromotriphenylene is used instead of the flame retardant, and the rest is the same as Example 1.

[0067] Comparative Example 2

[0068] The difference between Comparative Example 2 and Example 1 is that kraft lignin and hydroxyapatite are used instead of modified hydroxyapatite, the mass ratio of kraft lignin to hydroxyapatite is 1:1, and the rest is the same as Example 1.

[0069] Comparative Example 3

[0070] The difference between Comparative Example 3 and Example 1 is that magnesium chloride is not used in the preparation process of modified hydroxyapatite, and the other preparation conditions are the same as Example 1.

[0071] 3. Experimental examples

[0072] The properties of the materials obtained in Examples 1-3 and Comparative Examples 1-3 were tested, and the specific test indicators and test methods are as follows:

[0073] Tensile strength: refer to GB / T 528-2009 for testing, test three times in parallel, and take the average value of the results. For specific results, see Table 1;

[0074] Bending strength: refer to GB / T 9341-2000 for testing, test three times in parallel, and take the average value of the results. For specific results, see Table 1;

[0075] Limiting oxygen index: refer to GB / T 2406-2009 for detection, parallel test three times, the results are averaged, see Table 1 for specific results.

[0076] Table 1 Performance results of the materials obtained in Examples 1-3 and Comparative Examples 1-3

[0077]

[0078] It can be seen from Table 1 that the materials obtained in Examples 1-3 have excellent flame retardant properties and mechanical properties.

[0079] Compared with the materials obtained in Examples 1-3, the flame retardant properties of the materials obtained in Comparative Example 1 using 2,3,6,7,10,11-hexabromotriphenylene instead of the flame retardant of the present invention are significantly reduced. It is analyzed that the flame retardant of the present invention improves the flame retardancy of the polyurethane composite material through a dual flame retardant mechanism. Specifically, the flame retardant contains 1,2,4-triazole groups, sulfonyl groups and benzene rings, which improve the flame retardancy of the polyurethane composite material by promoting the formation of carbon black on the one hand, and can also improve the flame retardancy of the polyurethane composite material by diluting and inhibiting the release of combustible gases on the other hand.

[0080] Compared with the materials obtained in Examples 1-3, the mechanical properties of the materials obtained by using kraft lignin and hydroxyapatite instead of modified hydroxyapatite in Comparative Example 2 and adjusting the preparation process of modified hydroxyapatite in Comparative Example 3 are significantly reduced. Analysis shows that the surface of modified hydroxyapatite is rich in active sites such as carboxylic acid, hydroxyl and magnesium ions, which can interact with the polyurethane matrix and glass fiber. This interaction not only enhances the compatibility between the components, but also promotes more uniform dispersion and filling of the components, which is beneficial to improving the overall mechanical properties of the composite material.

[0081] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A polyurethane composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 45-65 parts of thermoplastic polyurethane elastomer, 20-30 parts of glass fiber, 10-15 parts of flame retardant, 1-5 parts of modified hydroxyapatite, 1-1.5 parts of dispersant, 1-1.5 parts of antioxidant and 1-3 parts of release agent; The preparation method of the flame retardant is as follows: 3-methylsulfonyl-1H-1,2,4-triazole-5-amine, triethylamine and dichloromethane are uniformly mixed to obtain a mixed solution; a dichloromethane solution of 2,3,6,7,10,11-hexabromotriphenylene is added to the mixed solution for reaction, and after the reaction is completed, a flame retardant is obtained by purification; The preparation process of the modified hydroxyapatite is as follows: The pretreated lignin is dispersed in deionized water, and then hydroxyapatite and magnesium chloride are added to obtain a mixed solution; after adjusting the pH of the mixed solution, the mixed solution is reacted at room temperature, and after the reaction is completed, the mixed solution is purified to obtain the mixed solution.

2. The polyurethane composite material according to claim 1, characterized in that: The molar ratio of the 3-methylsulfonyl-1H-1,2,4-triazole-5-amine, triethylamine and 2,3,6,7,10,11-hexabromotriphenylene is (6-6.5):(7-8):1; the molar concentration of 3-methylsulfonyl-1H-1,2,4-triazole-5-amine in the mixed solution is 0.5-0.6 mol / L; the molar concentration of 2,3,6,7,10,11-hexabromotriphenylene in the dichloromethane solution of 2,3,6,7,10,11-hexabromotriphenylene is 0.2-0.5 mol / L; the reaction temperature is 0-5°C, and the reaction time is 8-10h.

3. The polyurethane composite material according to claim 1, characterized in that: The mass ratio of magnesium chloride, pretreated lignin and hydroxyapatite is 1:(2-5):(2-5); the pH of the mixed solution is adjusted to 8-9; and the reaction time is 12-18 hours.

4. The polyurethane composite material according to claim 3, characterized in that: The preparation process of the pretreated lignin is as follows: According to the dosage ratio of kraft lignin and 1,4-dioxane aqueous solution of 1g: (45-55)mL, kraft lignin and 1,4-dioxane aqueous solution are mixed evenly, and then ozone is introduced into the mixture for reaction for 0.5-1.5h. After the reaction is completed, the mixture is purified to obtain the product; the volume ratio of 1,4-dioxane to deionized water in the 1,4-dioxane aqueous solution is 9:

1.

5. The polyurethane composite material according to claim 1, characterized in that: The dispersant is vinyl bisstearamide, the antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, and the release agent is Taoxi 3527.

6. The method for preparing the polyurethane composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The raw materials are mixed according to the weight ratio of each raw material, and then poured and solidified into a shape.

7. The method for preparing the polyurethane composite material according to claim 6, characterized in that: The stirring temperature is 160-175° C., the stirring time is 10-15 h, and the stirring speed is 250-500 rpm.

8. Use of the polyurethane composite material according to any one of claims 1 to 7 in a transmission tower.

Citation Information

Patent Citations

  • Hydroxyapatite strength enhancement based microfiber polyurethane man-made automobile leather and preparation method thereof

    CN105525511A

  • Process method for producing damping base plate

    CN116769271A